2009
DOI: 10.1111/j.1399-3062.2009.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Proptosis in a post‐renal transplant patient with disseminated tuberculosis

Abstract: A 55-year-old male patient 13 years post living-related renal transplant on immunosuppressives presented with prolonged fever and a recent protrusion of the right eyeball. Evaluation revealed disseminated tuberculosis with a tuberculoma in the right orbit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…However, there have also been reported cases wherein nosocomial infection and donor transmission were the causes 10) . SOT patients who become afflicted with CNS tuberculosis after their transplant may have the disease for up to 11 years 5 19) . Also, while it is assumed that immunosuppression and comorbidities may further complicate the presentation of posttransplantation CNS tuberculosis, there is not enough number of reported cases to allow comment on potential differences in clinical presentation 12) .…”
Section: Discussionmentioning
confidence: 99%
“…CNS tuberculoma after SOT may present up to 11 years following transplantation [36,37]. Although immunosuppression and comorbidities probably complicate the presentation of posttransplantation CNS tuberculoma, too few cases have been reported to allow comment on potential differences in clinical presentation.…”
Section: Tuberculoma (Tuberculous Granuloma)mentioning
confidence: 99%